Application of E-Learning for Online Learning During the Covid-19 Pandemic at University of Pembangunan Panca Budi - Heri Kurniawan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
During the COVID-19 pandemic, all activities must be carried out at home as a result of the policy of restricting people's movement. As a result of this policy, all learning at the school and university levels must be carried out remotely or online. In particular, universities have not been able to carry out distance or online learning for all courses and all meetings. Of course, during the pandemic, it is a challenge for all universities to be able to carry out distance learning or online learning. So far, all universities in Indonesia are still implementing a blended learning system, or mixed learning between face-to-face meetings and online meetings. Usually 30% of face-to-face meetings and 70% online use e-learning. At University of Pembangunan Panca Budi, e-learning-based blended learning has been implemented and developed since 2012. Even though UNPAB's infrastructure and human resources are quite ready to carry out fully online learning during a pandemic, there are challenges that must be anticipated, namely student readiness. because most of the students are in the area. Keywords : (e-learning, distance learning, covid-19)